PENGARUH PRAKTIK KERJA INDUSTRI (PRAKERIN) TERHADAP KESIAPAN KERJA SISWA KELAS 12 SMK NEGERI 1 SOOKO MOJOKERTO - Vitri Novianti; Novi Marlena (Jurnal Pendidikan Tata Niaga (JPTN), 2025)
Job readiness is crucial for students' success in entering the workforce. Therefore, factors that can support student job readiness are needed. This study aims to analyze the influence of internship (PRAKERIN) on the job readiness of 12th-grade students majoring in business and management at SMKN 1 Sooko Mojokerto. The study used a descriptive quantitative method. The population was 199 12th-grade students majoring in business and management at SMKN 1 Sooko Mojokerto. A sample of 133 students was selected using probability sampling through a proportional stratified random sampling approach. A questionnaire was used via Google Forms as the instrument. Data analysis was conducted using SPSS version 25. The results showed that internship variables influence the job readiness of 12th-grade students majoring in business and management at SMKN 1 Sooko Mojokerto.